CPE435: Process Chemistry / College of Engineering - UiTM, College of Engineering (Universiti Teknologi MARA (UiTM), 2019)
This course is an advanced course in chemistry. The topics covered include acid-base reactions, chemical equilibrium, thermochemistry, electrochemistry and kinetics.